2008
DOI: 10.1371/journal.pone.0003146
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin T1-Dependent Genes in Activated CD4+ T and Macrophage Cell Lines Appear Enriched in HIV-1 Co-Factors

Abstract: HIV-1 is dependent upon cellular co-factors to mediate its replication cycle in CD4+ T cells and macrophages, the two major cell types infected by the virus in vivo. One critical co-factor is Cyclin T1, a subunit of a general RNA polymerase II elongation factor known as P-TEFb. Cyclin T1 is targeted directly by the viral Tat protein to activate proviral transcription. Cyclin T1 is up-regulated when resting CD4+ T cells are activated and during macrophage differentiation or activation, conditions that are also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 65 publications
(89 reference statements)
3
40
0
Order By: Relevance
“…Levels of Cdk9 were reduced slightly, which reflects the almost equivalent levels of CycT1 and CycT2 in these cells. Similar downregulation of Cdk9 in vivo or in cultured cell lines was also reported by other researchers (24,37). Global gene expression profiles were examined with mouse whole-genome microarrays.…”
Section: Figsupporting
confidence: 78%
“…Levels of Cdk9 were reduced slightly, which reflects the almost equivalent levels of CycT1 and CycT2 in these cells. Similar downregulation of Cdk9 in vivo or in cultured cell lines was also reported by other researchers (24,37). Global gene expression profiles were examined with mouse whole-genome microarrays.…”
Section: Figsupporting
confidence: 78%
“…The overexpression of miR-27b also negatively affected HIV-1 replication. We previously showed that a large portion of cellular gene expression induced by T cell activation is in fact dependent upon cyclin T1 (53). We show here that the inhibition of individual miRNAs can increase cyclin T1 protein levels in resting CD4 ϩ T cells, indicating that miR-27b, -29b, -150, and -223 significantly contribute to repression of cyclin T1 in vivo.…”
Section: It Is Well Known That Cd4mentioning
confidence: 54%
“…However, cell lines are immortalized and possess abundant levels of NF-κB and P-TEFb. These important cellular transcription factors are limited in resting CD4+ T cells [21,44]. Therefore, it is important to verify that Euphorbia kansui is not just effective in cell lines.…”
Section: Resultsmentioning
confidence: 99%